Intramolecular Ring-Opening of Oxetanes: Access to Functionalised Hydroxymethyl 2,3-Dihydroimidazo[1,2-c]quinazolines - Bagal, Sharan K.; Bodnarchuk, Michael S.; King, Thomas A.; McKerrecher, Darren; Luo, Xuehong; Wang, Peng; Steward, Oliver R. (Synlett, 2020)
An intramolecular oxetane ring-opening was developed, affording novel 2-(hydroxymethyl)-2,3-dihydroimidazo[1,2-c]quinazolines from N-(3-methyloxetan-3-yl)quinazolin-4-amines under mild conditions. The resulting medicinally relevant tricyclic scaffolds were synthesised in good yields with diverse substituents. Moreover, reaction optimisation led to the development of a one-pot procedure.
Keywords: oxetane ring-opening; intramolecular cyclization; imidazoquinazolines; one-pot synthesis